2009
DOI: 10.1002/mnfr.200900110
|View full text |Cite
|
Sign up to set email alerts
|

GSTT2, a phase II gene induced by apple polyphenols, protects colon epithelial cells against genotoxic damage

Abstract: The potential protective effect of a polyphenol-rich diet for colon carcinogenesis is of great scientific and medical interest. Apples are a main source of polyphenols, and apple juice has been shown to attenuate chemically induced colon carcinogenesis in animal models. In addition to an antioxidant and antiproliferative activity, apple polyphenols have been shown to elevate expression of the phase II gene glutathione S-transferase T2 (GSTT2) in colon epithelial cells. We hypothesized that apple polyphenols ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 34 publications
0
22
0
Order By: Relevance
“…Petermann et al reported that Gstt2 protects cells from oxidative DNA damage induced by the synthetic hydroperoxide CumOOH, indicating that Gstt2 has anti-genotoxic function. [45] Therefore, we addressed the question of whether Setd7 protects against genotoxic stress by stabilizing Gstt2 expression. To analyze this, we challenged LNCaP and PC-3 cells with the Gstt2 substrate CumOOH.…”
Section: Discussionmentioning
confidence: 99%
“…Petermann et al reported that Gstt2 protects cells from oxidative DNA damage induced by the synthetic hydroperoxide CumOOH, indicating that Gstt2 has anti-genotoxic function. [45] Therefore, we addressed the question of whether Setd7 protects against genotoxic stress by stabilizing Gstt2 expression. To analyze this, we challenged LNCaP and PC-3 cells with the Gstt2 substrate CumOOH.…”
Section: Discussionmentioning
confidence: 99%
“…Apple polyphenols (a) inactivated pathogenic organisms in laboratory media (Fattouch et al, 2008;Wong et al, 2008;Du et al, 2011;Fratianni et al, 2011Fratianni et al, , 2012Friedman et al, 2013); (b) inactivated pathogenic bacteria on leafy greens (Moore et al, 2011) and in grilled beef patties (Rounds et al, 2012); (c) inhibited the biological activities of bacterial Shiga 2 toxin (Quiñones et al, 2009;Rasooly et al, 2010); (d) protected mice against infection by the influenza virus (He et al, 2011); and (e) protected cells against carcinogenic and genotoxic damage (Gerhauser, 2008;Petermann et al, 2009). …”
Section: Introductionmentioning
confidence: 98%
“…Neither AE[B] nor SPM induced GSTT2 or protected against CumOOH-induced DNA damage. Thus, we could not confirm a causal correlation between GSTT2 upregulation and protection against CumOOH found by others in genetically modified cells [52].…”
Section: Discussionmentioning
confidence: 79%